2001
DOI: 10.1124/mol.59.6.1464
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Opioid Binding to UDP-Glucuronosyltransferase 2B7 Fusion Proteins Using Nuclear Magnetic Resonance Spectroscopy

Abstract: The UDP-glucuronosyltransferase UGT2B7 is an important human UGT isoform that catalyzes the conjugation of many endogenous and exogenous compounds, among them opioids, resulting in the formation of D-glucuronides. The binding site of the aglycone is located in the N-terminal half of the protein. In this study, we demonstrate that the opioid binding site in UGT2B7 is within the first 119 amino-terminal amino acids. Two maltose binding protein fusion proteins, 2B7F1 and 2B7F2, incorporating the first 157 or 119 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…Since G211T was first identified in the present study, its functional effect remains unknown. Recently, Coffman et al (2001) demonstrated that the opioid binding site in UGT2B7 is within the first 119 amino-terminal amino acids (N-terminal half of the protein). The G211T mutation is the only identified mutation within this range.…”
Section: Discussionmentioning
confidence: 99%
“…Since G211T was first identified in the present study, its functional effect remains unknown. Recently, Coffman et al (2001) demonstrated that the opioid binding site in UGT2B7 is within the first 119 amino-terminal amino acids (N-terminal half of the protein). The G211T mutation is the only identified mutation within this range.…”
Section: Discussionmentioning
confidence: 99%
“…46 UGT2B7 is a major UGT responsible for the 3-and 6-glucuronidation of morphine in humans; 74,151,152 therefore, if this polymorphism led to variable rates of glucuronidation, a positive association would have been expected. Patel et al 24 once suggested the potential role of UGT2B7 polymorphisms in explaining interindividual differences in the biotransformation of oxazepam.…”
Section: Ugt2b7mentioning
confidence: 99%
“…Although this assay is homogeneous and therefore amenable to HTS applications, in its current format it is limited by low sensitivity, which could be improved by developing a more sensitive method of detection, such as luminescence. Another homogeneous assay uses NMR spectroscopy to detect the binding properties of substrates to the fusion UGT protein (Coffman et al 2001). One limitation of this type of study in terms of understanding the substrate specificity of the UGTs is that these assays fail to detect UGTs that bind the molecule but without glucuronidating it efficiently.…”
Section: Development Of Hts Assays For Ugtsmentioning
confidence: 99%